Seasonal and long-term consequences of esca grapevine disease on stem xylem integrity. (15th March 2021) - Bortolami, Giovanni; Farolfi, Elena; Badel, Eric; Burlett, Regis; Cochard, Herve; Ferrer, Nathalie; King, Andrew; Lamarque, Laurent J; Lecomte, Pascal; Marchesseau-Marchal, Marie; Pouzoulet, Jerome; Torres-Ruiz, Jose M; et al.
Abstract : Esca critically affects xylem water movement in grapevine perennial organs by the presence of plant-derived tyloses. Abstract: Hydraulic failure has been extensively studied during drought-induced plant dieback, but its role in plant-pathogen interactions is under debate. During esca, a grapevine ( Vitis vinifera ) disease, symptomatic leaves are prone to irreversible hydraulic dysfunctions but little is known about the hydraulic integrity of perennial organs over the short- and long-term. We investigated the effects of esca on stem hydraulic integrity in naturally infected plants within a single season and across season(s). We coupled direct ( k s ) and indirect ( k th ) hydraulic conductivity measurements, and tylose and vascular pathogen detection with in vivo X-ray microtomography visualizations. Xylem occlusions (tyloses) and subsequent loss of stem hydraulic conductivity ( k s ) occurred in all shoots with severe symptoms (apoplexy) and in more than 60% of shoots with moderate symptoms (tiger-stripe), with no tyloses in asymptomatic shoots. In vivo stem observations demonstrated that tyloses occurred only when leaf symptoms appeared, and resulted in more than 50% loss of hydraulic conductance in 40% of symptomatic stems, unrelated to symptom age. The impact of esca on xylem integrity was only seasonal, with no long-term impact of disease history. Our study demonstrated how and to what extent a vascular disease such as esca, affecting xylem integrity, could amplify plant mortality through hydraulic failure.